Coupling biocatalysis and click chemistry: one-pot two-step convergent synthesis of enantioenriched 1,2,3-triazole-derived diols - Cuetos, Aníbal (2013)
A fully convergent one-pot two-step synthesis of different chiral 1,2,3-triazole-derived diols in high yields and excellent enantio- and diastereoselectivities has been achieved under very mild conditions in aqueous medium by combining a single alcohol dehydrogenase (ADH) with a Cu-catalysed ‘click’ reaction.